Analysis of the Influence of Meteorological Factors on Rainfall Patterns in South Kuta - Rizal Afriadi Saragih; I Ketut Sukarasa; Pande Putu Hadi Wiguna; Komang Ngurah Suarbawa; Made Sumadiyasa; I Gusti Agung Widagda (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Rainfall in an area can be influenced by several meteorological factors, including the geographical location of an area, temperature, air pressure, air humidity, wind direction and speed, and other factors. This study aimed to analyze meteorological factors such as temperature, humidity, and air pressure, as well as wind direction and speed, on rainfall in South Kuta. The effect of temperature, pressure, and air humidity variations on rainfall was analyzed using IBM SPSS Statistics 25.0 software with the multiple linear regression method. The impact of wind direction on the distribution of rainfall in South Kuta was analyzed using WRPLOT View software version 8.0.2 with the windrose method. From the study, the multiple linear regression equation was obtained, namely Y = -175.008 + (-0.451) X₁ + 1.212X₂ + 0.094X₃ + 0.093X₄ with an R2 value of 12.8%, which indicates that only 12.8% of these meteorological factors affect rainfall where air humidity has the most dominant influence with a significance value of p <0.05. Wind direction impact analysis produces a windrose showing that during the rainy season, the dominant wind blows from the West, bringing high humidity. In the dry season, the dominant wind blows from the East, Northeast, and Southeast, bringing low humidity.